THE PIT DESIGN PLANNING AND PLANNING RESULT EVALUATION OF OVERBURDEN FRONT FROM WEST TO EAST USING MINESCAPE VERSION 5.7 SOFTWARE AT PT XYZ - Cahyadi, Roby; Iskandar, Isdaryanto; Aprianto, Diansah (International Journal of Social Science, 2022)
PT XYZ is a private company managed by foreign company was engaged in coal mining sector located in Muara Enim, South Sumatera. This company conducts open mining system or surface mining. The overburden volume production calculation applied by PT XYZ used software that is Minescape 5.7. Software. The objectives of this research was creating a front design of overburden from west to cast with elevation of #10 to 0 and the calculation of cut and fill volume of overburden planning and the joint result used Minescape 57. Software, comparing the amount of cut and fills volume and determining the factors causing the difference of the overburden volume calculation using Minescape 5.7. Software. The method used was material stockpiling method and disposal stability became the author's basis to recommend a disposal in pit which can accommodate safe product to be implemented in the field. Based on the calculation results using Minescape 5.7. Software in May, the obtained overburden volume was 587.36 BCM. From the analysis results related to the Minescape 5.7. Software calculation comparison between the progress and the joint of the cut was 428.62 and the fill was 20.48.